2013
DOI: 10.1016/j.canep.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Maternal pregnancy events and exposures and risk of hepatoblastoma: A Children's Oncology Group (COG) study

Abstract: Background Hepatoblastoma is a rare childhood liver cancer with an obscure etiology, however it is potentially associated with selected pregnancy events and hepatoblastoma risk in offspring. Methods Adjusted unconditional logistic regression estimated odds ratios (OR) and corresponding 95% confidence intervals (CI) for self-reported pregnancy events and medication use in a sample of mothers of 383 childhood hepatoblastoma cases and 387 controls. Results Risk of hepatoblastoma was significantly associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 12 publications
0
22
1
Order By: Relevance
“…15,16 Prepregnancy BMI and pregnancy weight gain have been found to correlate with maternal prenatal hormone levels [17][18][19][20] and hormonemediated cancer risk in offspring. 11,12,14,21,22 Data from the Utah Pregnancy Risk Assessment Monitoring System from 2000 through 2005 indicate a 19% rise in excessive pregnancy weight gain 23 ; these data also show that during the same time period, the proportion of women who were obese before pregnancy rose 25%. 24 Maternal BMI and gestational weight gain have previously been associated with increased risk for developmental disability.…”
Section: What This Study Addsmentioning
confidence: 88%
See 1 more Smart Citation
“…15,16 Prepregnancy BMI and pregnancy weight gain have been found to correlate with maternal prenatal hormone levels [17][18][19][20] and hormonemediated cancer risk in offspring. 11,12,14,21,22 Data from the Utah Pregnancy Risk Assessment Monitoring System from 2000 through 2005 indicate a 19% rise in excessive pregnancy weight gain 23 ; these data also show that during the same time period, the proportion of women who were obese before pregnancy rose 25%. 24 Maternal BMI and gestational weight gain have previously been associated with increased risk for developmental disability.…”
Section: What This Study Addsmentioning
confidence: 88%
“…[10][11][12][13][14] Steroid dysregulation characterizes the most common metabolic syndrome among reproductive-aged women, polycystic ovary syndrome, in which 40% to 80% of those affected experience excess weight. 15,16 Prepregnancy BMI and pregnancy weight gain have been found to correlate with maternal prenatal hormone levels [17][18][19][20] and hormonemediated cancer risk in offspring.…”
Section: What This Study Addsmentioning
confidence: 99%
“…We previously have described in detail the methods used in the COG case control study [Musselman et al, 2013; Puumala et al, 2012]. Hepatoblastoma cases were diagnosed at a COG institution between 2000 and 2008.…”
Section: Methodsmentioning
confidence: 99%
“…Characteristics of the study population and design have been previously reported (17, 18). Cases were identified through the Children’s Oncology Group (COG).…”
Section: Methodsmentioning
confidence: 99%